Analysis and Simulation of Wireless Ad-Hoc Network Routing Protocols - Mohamed, Abdul Haimid Bashir (2004)
An ad hoc network is a collection of wireless mobile nodes dynamically forming a temporary network without the use of any existing network infrastructure or centralized administration. Ad-hoc networks, characterized by dynamic topology. Each host moves in an arbitrary manner and routes are subject to frequent disconnection. During the period of route reconstruction, packets can be dropped. The loss of packets will cause significant throughput degradation. A number of routing protocols like Dynamic Source Routing (DSR), Ad Hoc On-Demand Distance Vector Routing (AODV) and Destination-Sequenced Distance-Vector (DSDV. have been implemented. In this project an attempt has been made using network simulator (NS) to compare the performance of two on-demand reactive routing protocols for mobile ad hoc networks: DSR and AODV, along with the traditional proactive DSDV protocol, using more stressful parameters, such as a very high mobility, large number of nodes and with a very heavy traffic loads.The simulation results show that at a small to medium field area with a considerably large number of nodes, the tabledriven DSDV protocol performs better than the On-demand protocols, AODV and